Gender Bias in Arabic: Analysis of Jacques Derrida's Deconstruction Theory l Al-Taḥayuz al-Jinsânĩy fĩ al-Lugah al-‘arabiyyah: Taḥlĩl Nazariyyah al-Tafkĩkiyyah Jacques Derrida - Dewi, Eva; Wargadinata, Wildana; Maimunah, Iffat; Ibrahim, Faisal Mahmoud Adam (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
Religious texts written in Arabic are created as a symbol that is not independent from the influence of cultural and social societies. Arab society, which adheres to the patriarchi system in their life, greatly affects every arrangement of their lives as well as Arabic language. It finally creates gender bias in the Arabic language. The gender bias has explicit symbol / word / sign in Arabic which is called function. Meanwhile, Islam itself contains the source of the Qur’an and hadith which are written in Arabic that strongly supports the dignity of women and men in equal rights and position. To answer the problem above, researchers used qualitative and descriptive research methods to express the form of words and language in context. Meanwhile, data analysis is analyzed by using the theory of disassociation Jacques Derrida to find discrepancies in the content of the text through three stages . The first stage, the verbal stage is a critical reading by finding paradoxes and contradictions in the text. The second stage, the textual stage, attempts to find a deeper meaning in the whole text. The third stage, the linguistic stage, is the stage in which the reader requests the appropriateness of the text, its error and its excessive language. The results of this research is expected to finding gender bias in Arabic language and the factors which cause the problems of gender bias in Arabic and our perspecitve of religous texts written in Arabic. Thus, this research is significant as it contributes in Arabic language.